2021
DOI: 10.1126/sciadv.abe0849
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Wnt/β-catenin signaling by SOX9 and Mastermind-like transcriptional coactivator 2

Abstract: Wnt/β-catenin signaling requires inhibition of a multiprotein destruction complex that targets β-catenin for proteasomal degradation. SOX9 is a potent antagonist of the Wnt pathway and has been proposed to act through direct binding to β-catenin or the β-catenin destruction complex. Here, we demonstrate that SOX9 promotes turnover of β-catenin in mammalian cell culture, but this occurs independently of the destruction complex and the proteasome. This activity requires SOX9’s ability to activate transcription. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 71 publications
3
20
1
Order By: Relevance
“…7b). The SOX4, as a positive regulator of the Wnt/β-catenin canonical pathway (Sinner et al, 2007), decreased over pseudo-time but SOX9, as a negative regulator (Sinha et al, 2021), increased (Fig. 7c), which is consistent with Fig.…”
Section: Resultssupporting
confidence: 87%
“…7b). The SOX4, as a positive regulator of the Wnt/β-catenin canonical pathway (Sinner et al, 2007), decreased over pseudo-time but SOX9, as a negative regulator (Sinha et al, 2021), increased (Fig. 7c), which is consistent with Fig.…”
Section: Resultssupporting
confidence: 87%
“…To test whether Defa5 was co-regulated by SOX9 and the Wnt pathway, we examined its expression in a HEK293 cell line with a DOX-inducible SOX9 overexpression construct (DOX-SOX9 cells) ( 20 ). We found that Defa5 mRNA levels were synergistically upregulated under high-Wnt, high-SOX9 levels induced by DOX treatment in conjunction with the β-catenin destruction complex inhibitor CHIR-99021 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In several different mammalian cell lines, the overexpression of SOX9 causes a reduction in Wnt transcriptional readouts and in β-catenin protein levels ( 1821 ). Recent work from our group found that SOX9 promoted β-catenin degradation in a destruction complex and proteasome-independent manner by transcriptionally activating the Notch pathway coactivator MAML2, which associates with β-catenin ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aquaporin 3 could inhibit the degradation of ECM and promote the proliferation of human nucleus pulposus cells, thereby alleviating IVDD, and these effects are partly related to the inhibition of wnt/β-catenin (Xie et al, 2016). In addition, β-catenin was inhibited when chondrocytes were infected with adenovirus-mediated SOX-9 gene in vitro (Sinha et al, 2021;Topol et al, 2009), which might be the key way for SOX-9 to promote ECM synthesis. In our study, puncture of annulus fibrosus decreased phosphorylation of Sox-9, BMP 2, and collagen 2, while increased expression of b-catenin, MMP-3, MMP-13, and ADAMTS5 in IVD, and these effects were attenuated by YQHXF intervention.…”
Section: Discussionmentioning
confidence: 99%